2020
DOI: 10.1007/s11440-020-01057-w
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of strip reinforced MSE walls

Abstract: This paper reports the results of 3D numerical modelling of a 6-m-high mechanically stabilised earth (MSE) wall constructed with concrete panels and steel or polymeric strip reinforcement. These systems pose numerical challenges as a result of the discontinuous reinforcement arrangement which is not the case for MSE walls constructed with continuous reinforcement layer configurations. Details of the numerical approach including modelling of the reinforcement strips, concrete facing panels and compressible bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Based on the findings of finite element simulations, the reactions of the ER walls to stress distribution, wall deflection, acceleration across the wall height, lateral wall displacement, lateral wall pressure, and backfill plastic strain have all been examined. The numerical modeling revealed that the boundary conditions, zone dimensions, and property assignment substantially influence the seismic response behavior of these wall types; these parameters play a critical role in the simulations of the models [5]. The connections comprise the following: (1) the horizontal and vertical connection of the bottom of the foundation soil; (2) the horizontal connection of the retained soil on both sides; and (3) the horizontal connection of the retained soil on its left side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the findings of finite element simulations, the reactions of the ER walls to stress distribution, wall deflection, acceleration across the wall height, lateral wall displacement, lateral wall pressure, and backfill plastic strain have all been examined. The numerical modeling revealed that the boundary conditions, zone dimensions, and property assignment substantially influence the seismic response behavior of these wall types; these parameters play a critical role in the simulations of the models [5]. The connections comprise the following: (1) the horizontal and vertical connection of the bottom of the foundation soil; (2) the horizontal connection of the retained soil on both sides; and (3) the horizontal connection of the retained soil on its left side.…”
Section: Methodsmentioning
confidence: 99%
“…The connections comprise the following: (1) the horizontal and vertical connection of the bottom of the foundation soil; (2) the horizontal connection of the retained soil on both sides; and (3) the horizontal connection of the retained soil on its left side. The confines of the FE model were established using the acceleration and displacement-controlled boundary option in ABAQUS [5,39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope and goals in which the numerical modeling of the reinforced soil wall can be useful is very wide [21][22][23][24][25][26][27][28][29][30][31]. Despite inefficient for regular/typical structures where analytical solutions are really fast and easy to use, numerical modelling can be used, as noted earlier, for design purposes [18].…”
Section: Numerical Analysis Of Reinforced Soil Wall Structuresmentioning
confidence: 99%
“…Moreover, because soil-facing interaction is also required in 3D analyses (e.g., the inside surface of the facing in reinforced soil wall modeling cases, FIGURE 3 | Load transfer from backfill soil to facing panel using PLAXIS: effect of the finite element mesh on the normal and shear stresses at the interface between the facing structure and backfill soil: (A) coarse mesh, (B) fine mesh, and (C) optimized mesh. Cases with Ri = 0.8 (Damians et al 2015b see Damians et al, 2021;Won and Lancuyan 2020;Montilla et al, 2022), 3D soil-facing interfaces should be used, subject to careful calibration and validation.…”
Section: Introductionmentioning
confidence: 99%